(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Neutrinos have provided us with new physics beyond the Standard Model of Particle Physics. This paper will mathematically calculate the mass of new species of Neutrinos. The Standard Model fails to explain many of the parameters that are the foundations of Particle Physics. Many of the Problems can be explained by adding mass to Neutrinos, and by finding new species of neutrinos.